Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1055/s-0039-1697862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EDTA and Phosphoric Acid Pretreatment on the Bonding Effectiveness of Self-Etch Adhesives to Ground Enamel

Abstract: Objectives:This in vitro study determined the effect of enamel pretreatment with phosphoric acid and ethylenediaminetetraacetic acid (EDTA) on the bond strength of strong, intermediary strong, and mild self-etching adhesive systems.Methods:Ninety sound human premolars were used. Resin composite cylinders were bonded to flat ground enamel surfaces using three self-etching adhesive systems: strong Adper Prompt L-Pop (pH=0.9–1.0), intermediary strong AdheSE (pH=1.6–1.7), and mild Frog (pH=2). Adhesive systems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Authors such as Rotta et al, Ibrahim et al argued that the pH of the acidic monomer embedded in the SEA might influence SBS results [9,21]. Therefore, Ibrahim et al found that intermediary strong SEA produced higher SBS values than mild and strong SEA [9]. However, their results do not agree with the present study, which found better SBS with the most acidic adhesive and that intermediary strength adhesives produced the lowest SBS values.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Authors such as Rotta et al, Ibrahim et al argued that the pH of the acidic monomer embedded in the SEA might influence SBS results [9,21]. Therefore, Ibrahim et al found that intermediary strong SEA produced higher SBS values than mild and strong SEA [9]. However, their results do not agree with the present study, which found better SBS with the most acidic adhesive and that intermediary strength adhesives produced the lowest SBS values.…”
Section: Discussioncontrasting
confidence: 67%
“…Authors such as Rotta et al, Ibrahim et al argued that the pH of the acidic monomer embedded in the SEA might influence SBS results [9,21]. Therefore, Ibrahim et al found that intermediary strong SEA produced higher SBS values than mild and strong SEA [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Samples were then prepared and examined on SEM as described above at ×2000. The enamel surface was classified by an experienced investigator, according to Cehreli and Altay[23] in:…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Therefore, enamel surface pretreatment needs to be improved to maintain clinically useful bond strengths while minimizing enamel loss; enamel surface pretreatment also needs to be simplified to reduce the bonding steps. 7,8 Various lasers have recently elicited considerable interest in the field of dentistry because of their function in the detection and removal of enamel caries, diagnosis of dental caries, cavity preparation, etching of teeth for resin bonding, demineralization prevention, root canal sterilization, and so on. [9][10][11] Lasers have received significant attention in resin bonding, especially in terms of their roughness and demineralization prevention effect on dental hard tissues.…”
Section: Introductionmentioning
confidence: 99%